Age-related changes in the phenotype of microglia - Imraish, Amer (2018)
Microglia play a central role in immune surveillance and modulation of neuroinflammation as well as playing a role in neurodevelopment. Microglia involve in the development of pathological pain in adults but not early in life. However little detail is known about the changing phenotype of microglia during development. We examined age-related changes in microglia following activation with pathogen- and damage- associated molecular patterns (PAMPs/DAMPs). Microglial cultures were prepared from neonatal postnatal day (P1) and adult (P40) rat brains and spinal cords. Immunocytochemistry, qRT-PCR and functional assays were used to identify age-related differences. Adult microglia display a pro-inflammatory immune profile characterized by significantly increased IL-1β mRNA levels in response to PAMPs and DAMPs. In contrast, IL-1β mRNA in neonatal microglia showed a slight increase after stimulation with DAMPs. Anti-inflammatory gene expression was significantly increased in neonatal microglia relative to adult microglia. Compared to adult microglia, neonatal cells had increased phagocytic activity when unstimulated and following activation with LPS and ATP. Moreover, the nuclear receptor Nurr1 may play a major role in reducing pro-inflammatory signalling and promoting the anti-inflammatory phenotype in neonatal microglia. Nurr1 isoforms are differentially expressed in neonatal and adult microglia, with the Nurr1a isoform being significantly elevated in neonatal cells. Using lentiviral vector-mediated expression of Nurr1 isoforms, we also show that over-expression of TINUR, a splice variant of Nurr1, in neonatal and adult microglia attenuates inflammation by trans-repression the IL-1β expression and trans-activation the IL-10 gene expression following ATP exposure. Together, these data provide evidence for age-related difference in microglial function during postnatal development. In addition, these findings demonstrate insight into the mechanisms by which Nurr1 might act, and suggest potential therapeutic targets for the treatment of neuro-inflammatory diseases.